The Behavior of Non-Destructive Test for Different Grade of Concrete - Abdul Rahim, Mustaqqim; Shahidan, Shahiron; Lee , Choon Onn; Saiful Bahari, Nur Amira Afiza; Abd Rahman, Norashidah; Ayob, Afizah (International Journal of Integrated Engineering, 2020)
Rebound hammer are prefer as non-destructive testing methods; where compression test as destructive test. A general series of tests for rebound hammer and destructive test was carried out at heavy concrete laboratory to obtain the desire result. A set of concrete cubes of sizes 100 x 100 x 100 mm had been casted and subjected to water curing which was held for 7, 14, 21 and 28 days to get the exact result of cube strength and rebound number. Rebound hammer testing were initially done before the compression test. The data obtained from each test has been evaluated and tabulated in this report. From this research, the variation between predicted strength and experimental strength for rebound hammer testing was 1.6%. This indicated rebound hammer testing managed to predict the strength more accurately. However, non-destructive test shown a margin of less than 10% error compare to destructive test.